Key ESG factors driving global sustainability in the shipping industry - Neolini Diamantara (Politeknik Pelayaran Banten, 2025)
Environmental, Social, and Governance (ESG) criteria have become a central mechanism for assessing corporate sustainability, while the United Nations Sustainable Development Goals (SDGs) provide a universal framework for addressing global challenges. Aligning these two frameworks is essential for shipping companies, as unclear prioritization of ESG criteria may lead to ineffective allocation of resources or missed opportunities to generate meaningful sustainability outcomes. This study aims to identify which ESG criteria—and their associated practices—within the commercial shipping sector contribute most significantly to global sustainability by mapping their alignment with relevant SDGs. This qualitative research employs document analysis, drawing from peer-reviewed scientific literature retrieved through Google Scholar and Scopus, as well as professional and industry sources produced by maritime practitioners across ship design, operations, management, crewing, training, classification, finance, and insurance. The documents analyzed include technical standards, guidelines, regulations, policies, reports, and commentary on industry trends. The findings highlight the ESG practices with the strongest contribution to sustainability, offering shipping companies clearer direction for prioritizing actions that deliver the highest global impact.